Solvophobicity-directed assembly of microporous molecular crystals - Hiroshi Yamagishi (Nature Portfolio, 2021)
Porous organic crystals can be challenging to prepare, because in the absence of guests, they often collapse into denser, non-porous polymorphs. Here the formation of porous and non-porous polymorphs in different solvents is shown to depend on a solvophobic effect driven by dispersion interactions.